Artificial Intelligence in Water Desalination: A Novel Approach for Global Sustainability - Mahadeva Rajesh; Patel Vivek; Ghosh Abhijeet; Dixit Saurav; Suthar Bhivraj; Gupta Vinay; Awaar Vinay Kumar; Bharadwaj Y.V.; Gupta Manish; Haranatti Jagadish Shrisaila; Arora Rishab (E3S Web of Conferences, 2023)
Artificial intelligence (AI) is an efficient technique frequently used to tackle practical issues in various engineering and medical fields. Apart from different areas, water desalination is essential in surviving humans, animals, and plants. It is a crucial industry for a sustainable planet, and we cannot live without water. As a result, engineers and researchers are quite active in this area. Recent studies based on Elsevier’s Scopus database demonstrate how automation using emerging technologies has enhanced the traditional desalination process. AI offers enormous potential to address numerous problems and real-time optimization procedures. According to Elsevier’s Scopus database, water desalination has extensively used AI optimization tools, especially after 2010, such as artificial neural networks (ANN), genetic algorithms (GA), fuzzy logic, and natural swarm global optimization techniques to improve water quality and quantity. Finally, it was determined that AI technologies would surely pave the way for better operation, water resource management, and process automation in the water sector in an increasingly unstable climate.